Migration policy as a factor influencing the USA presidential election - Gyulnara I. Gadzhimuradova; Kirill O. Sumin (Наука. Культура. Общество)
The article presents the transformation of US migration policy and analyzes its impact on the balance of power in the 2024 presidential election campaign. The 2024 election campaign in the US is characterized by significant differences between the major parties and their voters, as well as an emphasis on key economic and immigration issues that have divided American society. Mexico is the main labor donor to the US, and it is also a gateway for illegal migration from Latin America and Southeast Asia. Almost all the time of the existence of the United States, the immigration policy of the country shows that migration plays an important role in the development of American society. The problem of illegal migration has always existed and continues to have a significant impact on the socio-economic development of the country. The current U.S. immigration strategy combines continuity with restrictive measures, while seeking to adapt migration flows to the economic needs of the country. The article analyzes the impact of migration policy on the U.S. political landscape during the 2024 election campaign. Migration policy in the United States today is a tool for conducting political struggle and "settling scores". Illegal migrants from Latin American countries will have a particular impact on the upcoming elections, so a characteristic feature of the 2024 election campaign is a cross-party struggle for the Latin American electorate, coupled with tougher migration policies. The authors draw attention to the reasons for the transformation of the US migration system and give their forecast regarding the outcome of elections in the country under certain conditions.